The influence of beliefs upon pre-service teachers’ professional identity - Monica Ella Harendita; Truly Almendo Pasaribu (Intelektual Pustaka Media Utama, 2019)
Bearing in mind the interplay between beliefs and professional identities, constantly re-examining teachers’ beliefs is deemed to be significant in teachers’ identity formation. However, not much attention has been given to pre-service teachers’ beliefs. Through a case study, this research sought to reveal some beliefs held by four pre-service teachers doing their teaching practicum at a state junior high school in Yogyakarta. In addition, this study also attempts to describe the interplay between beliefs and the professional identity of those pre-service teachers’. Participants’ reflections, observations, and a focus group discussion were employed in order to figure out the answers to the research questions. The findings show that each of the participants processed the experiences they had in their teaching practicum differently. They started their teaching with pre-existing beliefs that were either confirmed or confronted when they did their practicum. The findings of this study also suggest that the interplay between beliefs and professional identity is complex. Not all beliefs were clearly reflected in the participants’ teaching performances. Some may seem contradictive to their beliefs. It implies that although the participants had sets of beliefs in their minds, teaching itself does not only represent their beliefs, but also serves as a stage where many intertwined factors occur.